2017
DOI: 10.1039/c7ra04504b
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and thermal properties of crosslinked polyurethane/lauric acid composites as novel form stable phase change materials with a low degree of supercooling

Abstract: In this article, a series of crosslinked polyurethane/lauric acid composites was prepared as form stable phase change materials (FSPCMs) through a brief and solvent-free method. In the FSPCMs, lauric acid functioned as a phase change substance, and crosslinked polyurethane simultaneously functioned as a supporting material and phase change substance. Compared with traditional supporting materials in FSPCMs, the crosslinked polyurethane here obviously reduces the loss of latent heat from the supporting material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…The second way is utilizing synergistic crystallization of PCMs. Kong et al prepared a composite PCM containing PEG‐based polyurethane (PU) and lauric acid (LA). Because of the synergy crystallization (overlap of the phase change process of PEG and LA), the supercooling degree was reduced.…”
Section: Introductionmentioning
confidence: 99%
“…The second way is utilizing synergistic crystallization of PCMs. Kong et al prepared a composite PCM containing PEG‐based polyurethane (PU) and lauric acid (LA). Because of the synergy crystallization (overlap of the phase change process of PEG and LA), the supercooling degree was reduced.…”
Section: Introductionmentioning
confidence: 99%
“…This was because the starch has swollen enough via the pyridine at the reaction temperature that provided access for the substitution of OH with lauric acid to occur in regions that are not otherwise accessible. Additionally, a small new peak emerged at 2θ of 8° that could be attributed to the crystallization of laurate . Kong et al reported similar crystallization of lauric acid in polyurethane (PU) conjugates as a result of a combination of peaks of PU and lauric acid substituent.…”
Section: Resultsmentioning
confidence: 98%
“…Additionally, a small new peak emerged at 2θ of 8° that could be attributed to the crystallization of laurate . Kong et al reported similar crystallization of lauric acid in polyurethane (PU) conjugates as a result of a combination of peaks of PU and lauric acid substituent.…”
Section: Resultsmentioning
confidence: 98%
“…Form‐stable composite PCMs can also be fabricated by encapsulating PCMs within polymer‐based materials with a network structure via melt blending or vacuum impregnation. Researchers have prepared form‐stable composite PCMs using various supporting components such as high‐density polyethylene (HDPE), low‐density polyethylene (LDPE), polypropylene (PP), acrylic resins, poly(methyl methacrylate) (PMMA), epoxy, polyurethane (PU), and poly(vinyl chloride) (PVC) …”
Section: Encapsulation Of Solid–liquid Pcmsmentioning
confidence: 99%